Sex differences in Huntington's disease from a neuroinflammation perspective - Risby-Jones, Grace; Lee, John D.; Woodruff, Trent M.; Fung, Jenny N. (Frontiers in Neurology, 2024)
Huntington's Disease (HD) is a debilitating neurodegenerative condition characterized by motor, cognitive and psychiatric abnormalities. Immune dysregulation, prominently featuring increased immune activity, plays a significant role in HD pathogenesis. In addition to the central nervous system (CNS), systemic innate immune activation and inflammation are observed in HD patients, exacerbating the effects of the Huntingtin (HTT) gene mutation.Recent attention to sex differences in HD symptom severity underscores the need to consider gender as a biological variable in neurodegenerative disease research. Understanding sexspecific immune responses holds promise for elucidating HD pathophysiology and informing targeted treatment strategies to mitigate cognitive and functional decline. This perspective will highlight the importance of investigating gender influence in HD, particularly focusing on sexspecific immune responses predisposing individuals to disease.